Palbociclib enhances the effect of doxorubicin-induced apoptosis in activated B-cell–like diffuse large B-cell lymphoma cells. Issue 2 (6th October 2023) - Yi, Liuying; Hu, Linhui; Huang, Keke; Li, Qian; Wang, Yangyang; Wang, Jiyu; Zhai, Zhimin
Abstract : Diffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma around the world. While R-CHOP has significantly improved patient outcomes, a subset of patients still has poor outcome. Here, the oncogenic roles of cyclin dependent kinase 4/6 (CDK4/6)-Cyclin D (CCND) signaling axis in DLBCL and its potential mechanism were investigated to explore the possibility of targeting CDK4/6-CCND signaling axis for DLBCL therapy. The transcription levels, functional enrichment analysis, mutation analysis, and prognostic values were performed via the Oncomine, GEPIA, UALCAN, cBioPortal, and Metascape and GenomicScape databases. Expression of CDK4/6-CCND signaling axis in DLBCL patients and DLBCL cell lines was evaluated by qRT-PCR. Additionally, the impact of CDK4/6-CCND signaling axis on cell viability and apoptosis in DLBCL cell lines were evaluated in vitro . The transcription levels of CDK4/6-CCND signaling were increased in DLBCL patients. Meanwhile, in Gene Expression Omnibus dataset, the expression of CDK4 and CCND2 was higher in ABC-DLBCL, whereas the expression of CCND1 and CCND3 was higher in GCB-DLBCL. Moreover, according to the results of qRT-PCR, the expression of CDK4/6-CCND signaling axis in ABC-DLBCL cell line is higher than that in GCB-DLBCL cell lines. Prognostic analysis indicated that upregulation of CDK4, CCND2, and CCND3 was significantly associated with poor survival. Cell function experiments showed that palbociclib could enhance the apoptosis-promoting and cell viability-inhibiting effects of doxorubicin on ABC-DLBCL (SU-DHL-2) cells. Doxorubicin accumulation experiment showed that palbociclib promoted doxorubicin accumulation in ABC-DLBCL cells. Additionally, Western blot analysis demonstrated that palbociclib prevented antiapoptotic protein BCL2 expression in ABC-DLBCL cell line. Our study provides novel insights into targeted therapies for ABC-DLBCL patients.